2017
DOI: 10.1016/j.cell.2017.04.016
|View full text |Cite
|
Sign up to set email alerts
|

An Immune Atlas of Clear Cell Renal Cell Carcinoma

Abstract: SummaryImmune cells in the tumor microenvironment modulate cancer progression and are attractive therapeutic targets. Macrophages and T cells are key components of the microenvironment, yet their phenotypes and relationships in this ecosystem and to clinical outcomes are ill defined. We used mass cytometry with extensive antibody panels to perform in-depth immune profiling of samples from 73 clear cell renal cell carcinoma (ccRCC) patients and five healthy controls. In 3.5 million measured cells, we identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
797
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 832 publications
(880 citation statements)
references
References 65 publications
34
797
2
3
Order By: Relevance
“…In agreement with recent studies (Chevrier et al, 2017; Lavin et al, 2017), we found a large degree of variation in the immune composition of each tumor (Figure 1D). For example, the myeloid and T cell fractions constituted 4–55% and 21%–96%, respectively.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with recent studies (Chevrier et al, 2017; Lavin et al, 2017), we found a large degree of variation in the immune composition of each tumor (Figure 1D). For example, the myeloid and T cell fractions constituted 4–55% and 21%–96%, respectively.…”
Section: Resultssupporting
confidence: 93%
“…Recent studies of human immune cells in lung adenocarcinoma and clear cell renal cell carcinoma using mass cytometry (Chevrier et al, 2017; Lavin et al, 2017) and bulk RNA-seq analysis of tumor-resident immune cells (Senbabaoglu et al, 2016) have provided broad characterization of the composition of main immune cell subsets. Further studies employing single-cell RNA-seq analysis have begun to explore finer definitions of immune cell subsets in tumors (Tirosh et al, 2016; Zheng et al, 2017), but their scale has been limited.…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of paired tumor and blood samples from patients being treated with ICB therapy may provide critical insight into these issues. Examination of additional parameters, such as costimulatory molecules, may offer additional clarity by providing an even finer resolution catalog of T cell subsets, as in recent analyses of renal cell carcinoma(Chevrier et al, 2017). …”
Section: Discussionmentioning
confidence: 99%
“…Mass cytometry allows for the interrogation of greater than 40 analytes at single cell resolution and enables systematic identification of complex cellular populations using high-dimensional analyses(Newell and Cheng, 2016; Tanner et al, 2013). Mass cytometry driven approaches have been utilized to characterize cellular processes including hematopoiesis, immune cell differentiation, and leukemic disease progression(Bendall et al, 2011; Spitzer and Nolan, 2016); and more recently, to analyze the immune infiltrates of solid tumors(Chevrier et al, 2017; Lavin et al, 2017; Leelatian et al, 2017; Spitzer et al, 2017). Here, we leverage mass cytometry to comprehensively characterize the cellular mechanisms of ICB in human melanoma and murine syngeneic transplantable tumor models.…”
Section: Introductionmentioning
confidence: 99%
“…Mouse models of DKD and in vitro studies also are warranted to confirm and validate the human data. Furthermore, with the development of high sensitive technologies such as global DNA methylations, 80 singular-cell RNA sequencing, 81 RNA bar-coding based on single-molecule fluorescence in situ hybridization, 82 MALDI-MSI, 33 laser capture micro-dissection -omics, 83 and cytometry by time of flight, 84 it becomes feasible to measure multiomics (ie, genomics, transcriptomics, proteomics, and metabolomics/lipidomics) data in a single-cell or cell type. In the near future, we could link pathologic changes with multi-omics in glomeruli, podocytes, and tubules of DKD, which will allow in-depth understanding of DKD and pave the path for personalized kidney precision medicine.…”
Section: Future Perspectivesmentioning
confidence: 99%